Association between anemia and acute lower respiratory tract infection in under-five children at Puducherry, India: a case control study - ., Gobinaath; J., Arun Daniel (International Journal of Contemporary Pediatrics, 2020)
Background: Anemia has been widely studied as an important factor in the immunity composition of under five children. The incidence of infections in children can be attributed to some extend to the prevalence of anemia among them. Hence this study aimed at exploring the association between anemia and lower respiratory tract infection (LRTI) among the 6 months to 5 years old children as an effort to establish anemia as an independent risk factor for LRTI. Methods: A case-control study was conducted among 200 children in the age group of 6 months–5 years who attended the out-patient and in-patient unit of the department of paediatrics during July to September 2019. Accordingly 100 cases of LRTI and 100 normal controls were age and gender matched and their parents were interviewed using a semi-structured questionnaire. Blood investigations were done and documented in a proforma. The association between anemia and LRTI was studied statistically. Results: Anemia was associated strongly with LRTI [odds ratio=4.96 (2.72, 9.1)] with 68% of the cases with LRTI manifesting anemia. The highest level of anemia was recorded among those with LRTI in the 25-42 months age group (80.8%) which was significantly (p<0.001) higher than controls. The mean hemoglobin level was 9.6±0.8 gm% among the cases which was significantly lower (p<0.001) than that of the controls (11.7±1.1 gm%). The mean iron level was 40±7.3 μg/dL among cases and 72±12.1μg/dL among the non-LRTI group (p<0.001). Conclusions: Anemia was significantly associated with LRTI group compared to the control group proving it to be an independent risk factor for LRTI.